Vitamin D may alleviate irritable bowel syndrome by modulating serotonin synthesis: a hypothesis based on recent literature - Yu, Xiao-Lan; Li, Cui-Ping; He, Lian-Ping (Frontiers in physiology, 2023)
A number of studies found that serotonin plays a vital role in the development of depression and irritable bowel syndrome. Recent studies showed that vitamin D was associated with regulating the synthesis of serotonin. This review focuses on the recent progress in the relationship between vitamin D and serotonin synthesis.